2020
DOI: 10.19082/7685
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-inflammatory and anti-angiogenesis effects of naloxone in the rat air pouch model of inflammation

Abstract: Background and objective: There is increasing evidence that the nervous system is in two-way interaction with the immune system. To study the relationship between the opioid and immune systems, the anti-inflammatory effect of naloxone -an opioid receptor antagonist -in the air pouch model as an animal model of rheumatoid arthritis was studied. Methods: Sterile air (20 and 10 ml) was subcutaneously injected into the back of the animals on days 1 and 3, respectively. On the 6 th day, carrageenan was injected int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…As a cofactor, LC involved in medium and long-chain fatty acids to pass into the mitochondrial matrix. Also, studies demonstrated that LC is an antioxidant and anti-inflammatory aspects in tissues without any side effect (10,11,(17)(18)(19). Since there are so little studies on the effects of LC tendon recovery, we aimed to research the effects of LC on an Achilles tendon injury model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a cofactor, LC involved in medium and long-chain fatty acids to pass into the mitochondrial matrix. Also, studies demonstrated that LC is an antioxidant and anti-inflammatory aspects in tissues without any side effect (10,11,(17)(18)(19). Since there are so little studies on the effects of LC tendon recovery, we aimed to research the effects of LC on an Achilles tendon injury model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, anti-inflammatory and antioxidant agents are expected to promote tendon repair (9). Experimental studies have shown that LC is a powerful antioxidant molecule with anti-inflammatory effects (10,11). Consequently, the purpose of this study is researched the functional and histological effects of LC on tendon recovery following experimental Achilles tendon injury.…”
Section: Introductionmentioning
confidence: 99%